2012
DOI: 10.1111/j.1949-8594.2011.00109.x
|View full text |Cite
|
Sign up to set email alerts
|

What Is STEM? A Discussion About Conceptions of STEM in Education and Partnerships

Abstract: Educational reformation has proceeded slowly despite the many calls to improve science and mathematics for our students. The acronym STEM (science, technology, engineering, and mathematics) has been adopted by numerous programs as an important focus for renewed global competitiveness for the United States, but conceptions of what STEM entails often vary among stakeholders. This paper examines the conceptions of STEM held by faculty members from a public Research I institution in the middle of a regional "STEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
469
1
62

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 702 publications
(544 citation statements)
references
References 8 publications
12
469
1
62
Order By: Relevance
“…Within such interdisciplinary philosophy, deep conceptual understanding and what is termed 21 st century skills could be developed (Biasutti & EL-Deghaidy, 2014). Despite the increased interest in STEM education, Breiner, Johnson, Harkness, & Koehler, (2012) claim that advocates have struggled to conceptualise its instructional practices. By a review of the literature, with an emphasis on STEM pedagogical implementation, there seems to be a struggle in incorporating all four disciplines (Atkinson & Mayo, 2010) as there is still a constant focus on integrating just science and mathematics.…”
Section: The Capacity To Integrate Knowledge and Modes Of Thinking Inmentioning
confidence: 99%
“…Within such interdisciplinary philosophy, deep conceptual understanding and what is termed 21 st century skills could be developed (Biasutti & EL-Deghaidy, 2014). Despite the increased interest in STEM education, Breiner, Johnson, Harkness, & Koehler, (2012) claim that advocates have struggled to conceptualise its instructional practices. By a review of the literature, with an emphasis on STEM pedagogical implementation, there seems to be a struggle in incorporating all four disciplines (Atkinson & Mayo, 2010) as there is still a constant focus on integrating just science and mathematics.…”
Section: The Capacity To Integrate Knowledge and Modes Of Thinking Inmentioning
confidence: 99%
“…A previous study that looked into STEM education showed the existence of a wide range of interpretations and conceptions by different stakeholders, ranging from K-12 school districts where it is seen as traditional disciplinary coursework composed of the subjects that make up STEM, to policy views most popularized by the National Science Foundation (NSF), to current understanding of the integration of the various disciplines as used in solving real-world problems (Breiner, Harkness, Johnson, & Koehler, 2012). The NSF, whose mission includes support for research and education in a number of STEM fields (except medical sciences), defines STEM broadly.…”
Section: Stem and Stem Educationmentioning
confidence: 99%
“…Reference [6] concludes that the main purpose of STEM education is to enhance one's ability to address STEM-related personal, social, as well as global issues. To do this, STEM education should emphasize on problem-based learning [7]. Apart from problem-solving, reference [8] mentions that STEM education is also necessary to produce students with the following knowledge and skills: innovation, creative, independent, logic, and IT-savvy.…”
Section: Introductionmentioning
confidence: 99%